KUALITAS PERAIRAN MUARA SUNGAI SIAK DITINJAU DARI PARAMETER FISIK-KIMIA DAN ORGANISME PLANKTON - Adnan Kasry; Nur El Fajri (Fakultas Perikanan dan Kelautan, Universitas Riau, 2012)
This research was conducted on August until October 2011 at estuary ofSiak River, Riau province. Aimed of this research to mesuered water quality atestuary of Siak river. Physically, have low water transparency and have high totalsolid (TSS), so that have influence to pH and low of water productivity.Keywords: Siak River, Physical, Chemical, Plankton